2017
DOI: 10.20944/preprints201703.0240.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypoxia and Inflammation in Cancer, Focus on HIF and NF-кB

Abstract: Cancer is often characterised by the presence of hypoxia and inflammation.Paramount to the mechanisms controlling cellular responses under such stress stimuli, are the transcription factor families of Hypoxia Inducible Factor (HIF) and NuclearFactor of kappa-light-chain-enhancer of activated B cells (NF-κB). Although, a detailed understating of how these transcription factors respond to their cognate stimulus is well established, it is now appreciated that HIF and NF-κB undergo extensive crosstalk, in particul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 104 publications
0
42
0
Order By: Relevance
“…While HDAC function has been associated with both hypoxia and inflammation, no association of SIN3A function has been reported with both Hypoxia or NF-κB mediated signalling pathways. However, we had previously demonstrated that hypoxia and NF-κB are part of an intricate crosstalk D'Ignazio et al, 2016;D'Ignazio et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…While HDAC function has been associated with both hypoxia and inflammation, no association of SIN3A function has been reported with both Hypoxia or NF-κB mediated signalling pathways. However, we had previously demonstrated that hypoxia and NF-κB are part of an intricate crosstalk D'Ignazio et al, 2016;D'Ignazio et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…These transcription factors dictate the production of inflammatory molecules such as cytokines and chemokines, in addition to activating COX‐2. This leads to further activation and recruitment of leukocytes, triggers the inflammasome of tumour cells, and stimulates the production of other inflammatory mediators in a vicious cycle (D'Ignazio, Batie, & Rocha, ). (Poly)phenols including OOPC do modulate signal transduction and might potentially block cellular hyperproliferation.…”
Section: Pharmacological and Nutraceutical Properties Of Htmentioning
confidence: 99%
“…Hypoxia condition triggered hypoxia response signalling in the stem cells. Hypoxia induced factor-1 alpha subunit are known as unstable protein in the normoxia condition, but for adapting hypoxia environtment HIF-1α are stabilized and the HIF signalling pathways are activated (Ignazio et al, 2017). HIF signalling pathways could induce cell dedifferentiation (Wang et al, 2017b).…”
Section: Cellular Plasticityand Dedifferentiationmentioning
confidence: 99%